High-resolution XRF analysis of sediment core IZN19-09 from Lake Iznik (NW Turkey) - Gastineau, Renaldo; Sabatier, Pierre; Fabbri, Stefano C; Anselmetti, Flavio S; Roeser, Patricia A; Findling, Nathaniel; Arnaud, Fabien; Şahin, Mustafa; Gündüz, Serkan; Franz, Sven-Oliver; De Sigoyer, Julia (In: Gastineau, R et al. (2021): Sedimentary and geochemical analyses from 14 sediment cores of Lake Iznik, NW Turkey [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.935167, 2021)
High-resolution XRF analysis of sediment cores (IZN19-05, IZN19-07, IZN19-09, IZN19-11, IZN19-13, IZN19-15, IZN19-20, IZN19-21, IZN19-22, IZN19-23, IZN19-24, IZN19-27, IZN19-28 and IZN19-29) from Lake Iznik, NW Turkey. The relative contents of major and trace elements were analysed with an X-Ray Fluorescence (XRF) Avaatech Core Scanner (EDYTEM Laboratory). The split-core surface was first covered with a 4-μm-thick Ultralene film to avoid contamination and desiccation of the sediment. All cores are registered in the French national cyber-core repository https://www.cybercarotheque.fr and the International Geo Sample Number (IGSN) service https://www.igsn.cnrs.fr/#/search. All cores were collected in April and July, 2019.
Keywords: Iznik; Lake; sediment; sediment core data; Turkey; XRF; XRF core scanner